Cataloguing and Classification Practices in Ghanaian Libraries - Alemna, A.A. (Ghana Library Journal, 1989)
This is a survey of the cataloguing practices of ten major libraries in Ghana. It concentrates among others, on the cataloguing and classification schemes used in the libraries, local adaptations, description of catalogue entries, the maintenance of card catalogues, and staffing. Various problems encountered in the Technical Services Departments are examined, and suggestions are made towards the improvement of cataloguing practices in the country’s library system.